Left behind by the G20? How inequality and environmental degradation threaten to exclude poor people from the benefits of economic growth - Fernández-Garayzábal González, Juncal (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2013)
Oxfam Briefing Paper, Intermon OXFAM. 19 de enero de 2012.